The Efficacy and Adverse Effects of Sugammadex and Neostigmine in Reversing Neuromuscular Blockade Inpatients with Obesity Undergoing Metabolic and Bariatric Surgery: A Systematic Review with Meta-Analysis and Trial Sequential Analysis - Shuangwen Wang; Yanjie Dong; Shuangcheng Wang; Yang Han; Qian Li (Medicina)
Background and Objectives: Metabolic and bariatric surgery (MBS) is practiced worldwide. Sugammadex was proven to have multiple benefits in reversing neuromuscular blockade (NMB) for patients with obesity undergoing MBS, but its effects on complications of various systems are not clear and concrete. Materials and Methods: This systematic review and meta-analysis was conducted as per the PRISMA guidelines and registered on the PROSPERO database (CRD42023491171). A systematic search was conducted in multiple databases for studies comparing sugammadex with neostigmine in MBS. Continuous data are reported as mean differences (MDs) and 95% confidence intervals (CIs). Dichotomous data are reported as relative risks (RRs) and 95% CIs. A two-sided p < 0.05 was considered statistically significant. Trial sequential analysis (TSA) was performed to evaluate the reliability of the conclusions. Results: Nine studies with 633 patients met the inclusion criteria. Compared with those from the neostigmine group, patients from the sugammadex group were characterized by a significantly shorter recovery time from the administration of the study drug to a train-of-four (TOF) ratio of ≥90% (MD [95% CI]: −15.40 [−26.64; −4.15]; I2 = 96.6%; p = 0.0073; n = 380; random effects model), a lower risk of postoperative residual curarization (PORC) (RR [95% CI]: 0.18 [0.09; 0.38]; p < 0.0001; I2 = 27.9%; n = 344; common effect model), postoperative nausea and vomiting (PONV) (RR [95% CI]: 0.67 [0.48; 0.93]; p = 0.0164; I2 = 0%; n = 335; common effect model), and cardiovascular complications (RR [95% CI]: 0.48 [0.26; 0.88]; p = 0.0186; I2 = 14.7%; n = 178; common effect model). TSA confirmed the conclusions regarding the recovery time and PORC risk. Conclusions: In conclusion, our systemic review and meta-analysis with TSA revealed that sugammadex provided a faster and more reliable choice to reverse NMB in patients with obesity undergoing MBS, with a lower risk of PORC. Sugammadex reduced the risk of cardiovascular complications and postoperative nausea and vomiting. However, the conclusions were not confirmed, and, so, further studies may be necessary.